MMPE: um método de modelagem de processo educacional basedo na modelagem de processo de negócio e na teoria da atividade - Luiz Carlos da Silva Luz (2009)
This work presents a method for requirements elicitation for educational software, called Method of Educational Process Modeling (MEPM), based on the methodology for Business Processes Modeling and the Activity Theory. By achieving an integration between Business Process Modeling and the Activity Theory, the MEPM defines the architecture of educational processes considering the structural and behavioral aspects of processes, the educational paradigm of teacher, the dynamics of processes educational, the activities performed by students and content addressed. The architecture of the educational process enables the definition of requirements that support the educational process in a consistent manner and promotes a better understanding of the process, the establishment of a common language between teachers and developers of software and the perception of innovations and improvements in process models. As an example of the applicability of the proposed method, we developed a study case to show how the information related to the process educational are obtained during the modeling and how they are used to obtain the requirements. The study also shows that the method provides the characterization of the educational paradigm of teacher, the description of the educational process and analysis of the participation of the software system in this process. Finally, we present the results, the contributions and future work associated with this work.